Diseño metodológico para la implementación de las 9S en plantas de producción (Revatex Industria Textil). - Chimborazo Chimborazo, Doris Vanessa (2021)
The current thesis research project was performed at Revatex Textile Industry, the same, which had as purpose: to design a 9 S implementation manual for contributing to a continuous improvement, the plant does not count with a quality system, so it has detected possible accidents that can happen within the production area, due to the conditions which is found, the incorrect area distribution from plant and machines avoids the staff displacement. This research is descriptive, since certain existing information could be used, the inductive method was used by considering the plant particularities and the bibliographic research technique was used for the 9 S information gathering, further, the field observation was used in order to determine the current Revatex processes. Finally, the survey technique was applied to workers in order to determine the nonconformities found in each job, in order to get that improvement. It was recommended changes and actions such as the shelves coding and of raw material, elaborating of a redesign plant and signage, in order to keep the plant into an organized, classified, clean and a good labor environment.